The Dynamics of Cultural Transmission and Curriculum Development in Indonesia - Adha, Idyana; Firman, Firman; Harun, Maizatul Mardiana (Universitas Trunojoyo Madura, 2023)
This article explores the dynamics of cultural transmission and educational curriculum development in Indonesia. In the context of Indonesia's cultural diversity, values such as gotong royong, religiosity, and local wisdom become the main foundation. The discussion includes the integration of cultural values in the curriculum, the drivers of character education, and the challenges of technological globalization. Technology and globalization play an important role in changing the way culture is conveyed and understood. Therefore, this article highlights the importance of technology-wise integration in the education curriculum, while maintaining the essence of local values. Community participation is a key element, emphasizing the need for collaboration with parents, communities and stakeholders to achieve harmony between local culture and global needs. National education policies also play an important role, and this article analyzes how policies can reflect community aspirations and support cultural transmission through the education system. Innovation and creativity are in focus, ensuring that curricula spur the development of critical and collaborative skills in line with local values. Overall, this article underscores the importance of a holistic approach involving the government, educational institutions, communities and relevant stakeholders in an effort to achieve an optimal balance between local traditions and global preparation. The dynamics of cultural transmission and curriculum development in Indonesia are key elements in shaping the next generation who not only understand, but also appreciate the nation's rich culture while preparing for global dynamics.